Structure, controlled release mechanisms and health benefits of pectins as an encapsulation material for bioactive food components. Issue 21 (14th October 2022) - Morales-Medina, Rocío; Drusch, Stephan; Acevedo, Francisca; Castro-Alvarez, Alejandro; Benie, Astrid; Poncelet, Denis; Dragosavac, Marijana M.; Defain Tesoriero, María Victoria; Löwenstein, Patricia; Yonaha, Verónica; Iturralde, Ramiro; Gauna Peter, Regina; et al.
Abstract : Depending on the chemical structure pectin may serve as protective shell material and as a prebiotic. Abstract : Encapsulation of food and feed ingredients is commonly applied to avoid the loss of functionality of bioactive food ingredients. Components that are encapsulated are usually sensitive to light, pH, oxygen or highly volatile. Also, encapsulation is also applied for ingredients that might influence taste. Many polymers from natural sources have been tested for encapsulation of foods. In the past few years, pectins have been proposed as emerging broadly applicable encapsulation materials. The reasons are that pectins are versatile and inexpensive, can be tailored to meet specific demands and provide health benefits. Emerging new insight into the chemical structure and related health benefits of pectins opens new avenues to use pectins in food and feed. To provide insight into their application potential, we review the current knowledge on the structural features of different pectins, their production and tailoring process for use in microencapsulation and gelation, and the impact of the pectin structure on health benefits and release properties in the gut, as well as processing technologies for pectin-based encapsulation systems with tailor-made functionalities. This is reviewed in view of application of pectins for microencapsulation of different sensitive food components. Although some critical factors such as tuning of controlled release of cargo in the intestine and the impact of the pectin production process on the molecular structure of pectin still need more study, current insight is that pectins provide many advantages for encapsulation of bioactive food and feed ingredients and are cost-effective.